Assessing curriculum integration in higher education through academics, undergraduates and employers’ feedback: the case of some countries from six continents - Illahibaccus-Sona, Shaima Banu; Abdullah, Mohammad Ridhuan (Emerald Publishing, 2025)
Purpose – This study aims to investigate the critical role of Curriculum Integration (CI) in higher education, addressing global concerns about university graduates’ readiness for the workforce. It explores the perspectives of undergraduates, academics and employers on CI across Asia, Africa, North America, South America, Europe and Australia. Design/methodology/approach – Using a mixed-method approach, the research combines quantitative surveys with qualitative interviews to comprehensively analyze CI’s impact. Data analysis involved SPSS and thematic methods, ensuring validity through triangulation, member checking, pilot testing and sensitivity analysis. Ethical considerations included informed consent and confidentiality. Findings – The study uncovers significant regional disparities in CI awareness and implementation, particularly between developed and developing regions. While CI’s benefits for holistic learning are widely acknowledged, few academics actively use it, citing barriers like time, funding and institutional resistance. Employers strongly support CI, highlighting its value in enhancing graduate employability skills, though regional differences demand localized approaches. Undergraduates prefer CI for its interactive, practical nature. The findings call for targeted faculty development and regional strategies to increase CI adoption, ultimately improving graduate employability. Originality/value – This global study provides a replicable framework for evaluating interdisciplinary educational reforms. By comparing CI’s impact across diverse systems, it offers a model applicable to other pedagogical approaches, notably project-based or competency-based education, underscoring the importance of region-specific strategies in educational reforms